2009
DOI: 10.1002/ajhb.20866
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of secular change in the human mandible over the last century

Abstract: In light of several recent investigations that have identified notable secular change in cranial size and morphology over the last century, the present study addresses its possible effects in the mandible in U.S. populations. Standard measurements of 407 mandibles from the Terry (Smithsonian) and Hamann-Todd (Cleveland Museum of Natural History) Collections, which are primarily composed of individuals living in the early 20th century, were compared with those of 595 mandibles from the Forensic Anthropology Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 7 publications
(7 reference statements)
6
30
0
2
Order By: Relevance
“…There are parallels here with studies of other archaeological samples. Compared to ancient populations, in more recent groups likely to have had softer diets symphysial heights have been reported as showing lesser reduction than other mandibular dimensions (Moore et al, 1968), no alteration (Martin and Danforth, 2009;Rando et al, 2014), or an increase (Fukase and Suwa, 2008;Kaifu, 1997). Pinhasi et al (2008) did find that symphysial height decreased with adoption of agriculture (and perhaps a softer diet) in the Levant.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…There are parallels here with studies of other archaeological samples. Compared to ancient populations, in more recent groups likely to have had softer diets symphysial heights have been reported as showing lesser reduction than other mandibular dimensions (Moore et al, 1968), no alteration (Martin and Danforth, 2009;Rando et al, 2014), or an increase (Fukase and Suwa, 2008;Kaifu, 1997). Pinhasi et al (2008) did find that symphysial height decreased with adoption of agriculture (and perhaps a softer diet) in the Levant.…”
Section: Discussionmentioning
confidence: 91%
“…Rando et al (2014), comparing Mediaeval and post-Mediaeval mandibles from London, report broadly similar findings. In skeletal material from North America, Martin and Danforth (2009) report greater corpus length but reduced gonia in late 20th century compared with early 20th century mandibles, and discuss progressively softer diet as a factor.…”
Section: Introductionmentioning
confidence: 95%
“…These differences in ramus flexure are likely the effect of changes in the magnitude of the force produced by the masseter muscle. The reduced lateral flexure in Middenbeemster is likely caused by the intake of an increased amount of soft food (Martin and Danforth, 2009). Thus, it seems reasonable to suggest that the softer diet was an important factor in both the decrease in average size of the mandible and a change in average shape.…”
Section: Homo -Journal Of Comparative Human Biology 68 (2017) 329-342mentioning
confidence: 99%
“…In contrast, the Brazilian sample was a contemporary, or modern, sample, with skulls and mandibles belonging to a collection originating from the 20th century. Considering the plasticity of the skull over time, anatomical evaluations indicate a decrease in cranial measurements 7, including a reduction of the facial breadth that results in narrower and elongated faces 1,15,18 and mandibles 5 . It is not possible to conirm that the results found in the present study are related to inter-populational variation or cranial plasticity due to the temporal differences between the samples.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the variations that have occurred and the intensity of these variations are speciic for each population and do not follow a universal parameter. Studies around the world have shown that several modiications of the skull have occurred over time [1][2][3][4][5][15][16][17][18][19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%